British economic and social history (1700 -1977) / by J. Walker - Walker, J. (Estover, 1979)
This book describes some of the more important social and economic changes that have arisen from the industrialisation of British society from the eighteenth century to the present day. But as surveys of social and economic trends cannot be confined within set periods, pre-1700 material has been included. The number of topics that have a claim for inclusion is very large; I have, therefore, been obliged to make a selection, choosing those which in my judgment will prove most helpful to Sixth Forms, and to students reading for the certifi cates and diplomas of the Department of Education and Science Joint Committee for National Awards in Business Studies. The book also, it is hoped, will be read by those members of the general public interested in the main currents of social and economic change. In order to assist readers towards some understanding of current social and economic issues I have written four chapters on post-1939 Britain. But in attempting to bring our island story up to date, I have, as will be readily understood, been in danger of being overtaken by events.
Keywords: Great Britain economic history